Gender differences in the usage and attitudes toward the internet among student teachers in a public Malaysian university - Wong, Su Luan; Ng, Siew Fung; Atan, Hanafi (Science Publications, 2008)
The problems of gender disparity in the usage and attitude towards the Internet have received considerable interest among researchers. Most findings have revealed that females are at a disadvantage compared to their male counterparts where Internet usage is concerned. They have unequal access, a low rate of usage and exhibit negative attitudes towards the Internet (Nachmias et al., 2000; Sherman et al., 2000; Madell & Muncer, 2004). Prompted by these observations, this study was carried out to investigate the gender disparity in Internet usage and the attitudes among 152 student teachers (80 females and 72 males) at a public Malaysian university (Universiti Putra Malaysia). The results of this study revealed no gender disparity in Internet usage; the female student teachers were found to spend as much time using the Internet as their male counterparts. These results accordingly contradicted the common findings of other researchers. The results also revealed that the students exhibited positive attitudes toward the Internet regardless of gender, again in contradiction to most other findings. Possible reasons and the implications of these findings will be elaborated and discussed.